Sport business models: a stakeholder optimization approach. Issue 1 (3rd November 2020) - Pittz, Thomas; Bendickson, Joshua S.; Cowden, Birton J.; Davis, Phillip E.
Abstract : Purpose: Owners of the US-based sport teams are seeing consistent gains on their financial investments, no matter the success of their teams on the playing field or their impact on the surrounding community. Sports teams are a part of an ecosystem comprised of primary and secondary stakeholders. The authors explore this phenomenon using a stakeholder perspective to understand how different business models and ownership structures optimize stakeholder value. Design/methodology/approach: The authors employ an evaluative conceptual approach to examine the dominant model in the US, European ownership structures and public-private partnerships (PPPs). T finalize these comparisons by exploring a fourth business model and ownership structure – a relatively unique option in the US deployed by the Green Bay Packers – which we refer to as the maximized value partnership (MVP). These comparisons are followed by practical advice for owners in regard to these governance mechanisms. Findings: The MVP ownership model has the potential to level the playing field between public and private actors. This potential is realized by fusing some of the best practices from European football clubs, in particular aspects of the stock market and supporter trust models. Originality/value: By evaluating the most common ownership structures for sports teams, t provide an alternative model as well as practical advice for owners.